(untitled) (American Journal of Interdisciplinary Research and Innovation, 2022)
The pressing problem on poverty have led the Philippine government to initiate program on poverty alleviation, and one of these programs is the Pantawid Pamilyang Pilipino Program (4Ps). Review of related studies revealed that there is a need to investigate the impact of this program. In this context, this case study was conducted to determine the impact of the 4Ps in terms of poverty reduction, social development, financial management, and livelihood empowerment. Through the use of an aide-mémoire, six (6) beneficiaries and their families were interviewed. Results of thematic analysis of the interview transcripts revealed that 4Ps program provides the families’ basic needs, promotes the families’ well-being, promotes their socioeconomic status, and provides capital for their livelihood. Clearly, the program had positive impact on the lives of the beneficiaries which characterizes the Ilokano phrase ‘Rang-ay Babaen ti 4Ps’ which means the improvement of the quality and status of the beneficiaries’ lives after adopting the 4Ps program.